La quinta esquina - Metter, I. (Izrailʹ) (Libros del Asteroide, 2014)
Boria, the narrator of this lovely novel, is a superfluous man fated to play a marginal role in society--Soviet Russian society. The son of a small Jewish businessman, his petit bourgeois origins prevent him access to the university world in which he believes he has found his calling. This means he must educate himself and resign himself to teaching in second-class institutions. In a fragmentary way, the sensitive Boria recalls his tumultuous life: the death of his father; his first attempts to earn a living teaching private lessons; living in different cities, including Kharkiv, Leningrad, and Rostov; and, above all, his love for the beautiful Katia, a paradigm of feminine unpredictability. Through these fragments, the narrator forms an emotional yet insightful portrait of daily life in Soviet Russia, a world dominated by collective values that tend to crush any glimmer of humanity. The author infuses biographical elements into the novel, which he finished writing in the 1960s but could not publish until 1989. The book established Métter as one of the most prominent Soviet authors of the era and earned him international fame.